A new approach to scientific computation - Symposium on a New Approach to Scientific Computation (1982 : IBM Thomas J. Watson Research Center); Kulisch, Ulrich; Miranker, Willard L.; International Business Machines Corporation (New York : Academic Press, 1983)
41